PELATIHAN DIGITAL MARKETING PENGEMBANGAN UMKM DI KEC. BANGKO KAB. MERANGIN - Angra Melina; Sarinah; Hayati; Ruwaiza Sasmita; Kusaimah; Fitri Kartika Sari (Hira Institute, 2024)
Traditional businesses have traditional marketing and sales channels but this will not reach a wider range of consumers. Therefore, it is necessary to carry out digital marketing training as an effort to develop UMKM. The method for implementing this training uses the Participatory Action Research (PAR) method. Based on the results of the evaluation carried out after carrying out the training, it shows that more than 75% of the training participants understand the use of digital marketing